The Seismic Performance Analysis of Semi-rigid Spatial Steel Frames Based on Moment-Rotation Curves of End-plate Connection. (February 2022) - Lu, Shengcan; Wang, Zhan; Pan, Jianrong; Wang, Peng
Abstract: With their efficiency and high ductility for energy consumption, end-plate connection steel frames (EPCSFs) are commonly used in high seismicity areas. With the aim to realise high-efficiency calculation of EPCSFs performance, this study proposes a simple and accurate model in OpenSees software for the end-plate connection (EPC) with a behaviour captured by nonlinear rational springs. Previous EPC test study and design criteria are summarised and provides a reasonable failure mode of the connection. In light of the summary, the moment-rotation curve model of the spatial connection is developed according to the component method. Three 1/4-scale specimens with EPC of the quasi-static cyclic test are carried out to verify the model accuracy and study the failure mode in the EPCSFs. According to the failure criteria, the mechanical characteristics and deformation of the specimen are studied. The bearing capacity, stiffness degradation, and plastic energy dissipation of the test specimen and OpenSees analytical model are also analysed and compared. The failure modes of the test specimens are consistent with the optimal ones of the EPCs, which satisfy the design criteria of 'strong column, weak beam'. The specimens perform well in the hysteresis characteristics and provide stable lateral stiffness and high ductility, with a mean ductility coefficient of all specimens is approximately μ = 5.086. This model supplies an accurate prediction of EPCSFs performance for significant savings on computational cost, and is thus extraordinarily useful for daily design by seismic performance analysis.